Evaluación Financiera en la Lubricadora y Lavadora La Esmeralda de la Ciudad de Loja, Periodo 2012-2013 - Labanda Puglla, Rosa Leticia (2016)
This thesis entitled "FINANCIAL ASSESSMENT AND WASHING MACHINE IN lubricator" EMERALD "LOJA CITY, PERIOD 2012-2013"; the same as it performed in compliance to pre-qualify the title of Engineer in Accounting and Auditing, Certified Public Accountant Auditor at the National University of Loja, thus adjusting to the rules of current academic system requirements. To comply with the objectives, a vertical and horizontal analysis was performed by determining the absolute or relative change that has suffered each item in the financial statements from one period over another, giving to know the increase or decrease of accounts and allowing define whether the behavior of the company was good or bad. For a further study of financial indicators it was applied: liquidity, activity and profitability with them it was possible to check and verify the actual financial situation in which the lubricator is, then proceeded to calculate the EVA, breakeven, NPV, IRR, measuring the degree of profitability of it, often performing projecting cash flow going in and out the product's own business activity. Inside the main contribution that can emphasize the financial evaluation of the company subject to study establishes that has in the fiscal year of 2012 its current assets reflect considerable value in the inventory account in the 5 amount of $ 329,454.31, and 2013 recorded a total of $ 317,114.36 in it. Highlighting that company resources are invested large amount of merchandise available for sale so as to enable timely and efficient to meet the needs of consumers. In addition to making an objective assessment and interpretation of accounting information applied different methods, whose results will contribute in some way to the financial strengthening of the lubricator, with the results obtained; thus improving service to the community. Finally, conclusions and recommendations are presented, suggesting the Manager-Owner to be performed continuously for a financial assessment that in this way the company under study uses its resources appropriately and relevant.